2012
DOI: 10.1179/1743289811y.0000000052
|View full text |Cite
|
Sign up to set email alerts
|

Cure monitoring through time–frequency analysis of guided ultrasonic waves

Abstract: Cure monitoring has received considerable interest for industrial applications that use thermosetting resins and advanced composites. In these applications, the degree of curing is critical for the structures' high quality and performance. This paper demonstrates the excitation of Lamb waves with low profile surface mounted piezoelectric transducers for the characterisation of symmetric composite laminates at different cure levels. The response signals were processed by extracting their instantaneous character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Moreover, a first observation is that as the cure level increases, the peak‐to‐peak amplitude of the IF increases. For the purpose of the current analysis, after the decomposition of the original time signals, the power spectrum of each corresponding IMF was plotted and the optimum one was selected according to how close its carrier peak was to the excitation frequency . The optimum IMF for all cure levels was IMF5, which was used for the subsequent analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a first observation is that as the cure level increases, the peak‐to‐peak amplitude of the IF increases. For the purpose of the current analysis, after the decomposition of the original time signals, the power spectrum of each corresponding IMF was plotted and the optimum one was selected according to how close its carrier peak was to the excitation frequency . The optimum IMF for all cure levels was IMF5, which was used for the subsequent analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Many methods have been successfully used to monitor the cure level, either based on the cure temperature measurement or on the molecular level assessment. An extensive literature review as well as a preliminary assessment of this approach can be found in literature . Damage detection on the other hand refers to the monitoring of the repair integrity for the estimation of flaws or damage of critical size.…”
Section: Introductionmentioning
confidence: 99%
“…Bulk wave contact ultrasound, usually conducted in pulse-echo mode in the low megahertz frequency range, can monitor the completion of resin cure based on when the time delay plateaus/ultrasonic velocity becomes constant value in graphite/epoxy composites [8] and epoxy resins [9]. Other ultrasonic phenomena have also been used for monitoring degree of cure including, attenuation (i.e., amplitude of signal) [7,8,[10][11][12][13], instantaneous phase, and the "mean value of each frequency curve weighted by the maximum corresponding spectral amplitude" [14].…”
Section: Introductionmentioning
confidence: 99%
“…A widely used and accepted technology in the structural health monitoring (SHM) of thin‐walled structures is to deploy the propagation of guided elastic waves for damage detection purposes . Named after their discoverer, Horace Lamb , they refer to elastic perturbations propagating in plate‐like structures.…”
Section: Introductionmentioning
confidence: 99%